The Mechanism of CO2 Insertion into Iridium(I) Hydroxide and Alkoxide Bonds: A Kinetics and Computational Study. Issue 18 (20th March 2015) - Truscott, Byron J.; Kruger, Hedi; Webb, Paul B.; Bühl, Michael; Nolan, Steven P.
Abstract The facile insertion of CO2 into iridium(I) hydroxide, alkoxide, and amide bonds was recently reported. In particular, [Ir(cod)(IiPr)(OH)] (IiPr=1, 3‐bis(isopropyl)imidazol‐2‐ylidene) reacted with CO2 in solution and in the solid state in a matter of minutes to give the novel [{Ir(cod)(IiPr)}2(μ‐κ1O:κ2O, O‐CO3)] complex. In the present study, this reaction is probed using kinetics and theoretical studies, which enabled us to analyse its facile nature and to fully elucidate the reaction mechanism with excellent correlation between the two methods.